Intra‐Amniotic Administration of HMGB1 Induces Spontaneous Preterm Labor and Birth. (January 2016) - Gomez‐Lopez, Nardhy; Romero, Roberto; Plazyo, Olesya; Panaitescu, Bogdan; Furcron, Amy E.; Miller, Derek; Roumayah, Tamara; Flom, Emily; Hassan, Sonia S.
Abstract : Problem: Sterile intra‐amniotic inflammation is associated with spontaneous preterm labor. Alarmins are proposed to mediate this inflammatory process. The aim of this study was to determine whether intra‐amniotic administration of an alarmin, HMGB1, could induce preterm labor/birth. Method of Study: Pregnant B6 mice were intra‐amniotically or intraperitoneally injected with HMGB1 or PBS (control). Following injection, the gestational age and the rates of preterm birth and pup mortality were recorded. Results: Intra‐amniotic injection of HMGB1 led to preterm labor/birth [HMGB1 57% (4/7) versus PBS 0% (0/6); P  = 0.049) and a high rate of pup mortality at week 1 [HMGB1 60.9 ± 11.7% (25/41) versus PBS 28.9 ± 12.6% (11/38); P  = 0.001). Intraperitoneal injection of HMGB1 did not induce preterm labor/birth. Conclusion: Intra‐amniotic administration of HMGB1 induces preterm labor/birth.